Nurses' perceptions of caring for parents of children with chronic medical complexity in the pediatric intensive care unit. (December 2017) - Denis-Larocque, Gabrielle; Williams, Karl; St-Sauveur, Isabelle; Ruddy, Margaret; Rennick, Janet
Highlights: Educational sessions on families with CMC may facilitate the transition of PICU nurses into the unique caregiving role of caring for parents of CMC. Discussing expectations and demonstrating respect for parents' preferences in their child's caretaking routine may empower parents of CMC. An open and transparent dialogue with parents of CMC may serve to enhance the nurse-parent partnership, especially in challenging moments. Abstract: Objectives: The aim of this study was to explore nurses' perceptions of caring for parents of children with medical complexity [CMC] in the pediatric intensive care unit [PICU]. Research methodology: An interpretive descriptive design was used to explore nurses' perceptions of caring for parents of CMC in the PICU. Semi-structured interviews were conducted with ten nurses. Interview data were collected and analyzed using qualitative inductive content analysis. Findings: Nurses revealed that their experiences of caring for parents of CMC evolved over time as they learned to tailor a caregiving partnership based on trust. Although various circumstances could challenge this partnership, nurses strove to maintain and nurture it through self-reflection and optimal communication. Three themes were identified in the data that captured PICU nurses' perceptions: (i) "Thrown to the wolves": Adjusting to a new caregiving role; (ii) "Getting to know each other": Merging caregiving roles; (iii) "Keeping connected": Working to preserve the partnership. Conclusions: Findings shed new light on the importance of a trusting nurse-parent partnership in caring for parents of CMC in the PICU. Results will be used to develop strategies to enhance this partnership, with the goal of supporting parents and staff in their caregiving roles.